Zarządzam przymusowe szczepienia ochronne A. przeciwko ospie - Lazarowicz, Leonard (1909-1973). (Gdynia : [s.n.], 1949)
Afisz inf. o szczepieniach.
Keywords: Ospa -- szczepienie -- Polska -- Gdynia -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- źródła